The carbon footprint of citrus exports via the Port of Durban: A container barge system analysis - Micah Burgstahler; Leila L. Goedhals-Gerber; Ben Human (Journal of Transport and Supply Chain Management)
Background: The Port of Durban in South Africa has faced significant road congestion for many years. To address this, the fresh-produce industry proposed a cross-harbour container-handling barge system. The citrus industry requested this study to evaluate the potential carbon footprint impact of such a system on citrus exports transported in reefer containers around the port.